The impact of malaria-protective red blood cell polymorphisms on parasite biomass in children with severe Plasmodium falciparum malaria - Uyoga, S; Watson, JA; Wanjiku, P; Rop, JC; Makale, J; Macharia, AW; Kariuki, SN; Nyutu, GM; Shebe, M; Mosobo, M; Mturi, N; Rockett, KA; et al. (Springer Nature, 2022)
Severe falciparum malaria is a major cause of preventable child mortality in sub-Saharan Africa. Plasma concentrations of P. falciparum Histidine-Rich Protein 2 (PfHRP2) have diagnostic and prognostic value in severe malaria. We investigate the potential use of plasma PfHRP2 and the sequestration index (the ratio of PfHRP2 to parasite density) as quantitative traits for case-only genetic association studies of severe malaria. Data from 2198 Kenyan children diagnosed with severe malaria, genotyped for 14 major candidate genes, show that polymorphisms in four major red cell genes that lead to hemoglobin S, O blood group, α-thalassemia, and the Dantu blood group, are associated with substantially lower admission plasma PfHRP2 concentrations, consistent with protective effects against extensive parasitized erythrocyte sequestration. In contrast the known protective ATP2B4 polymorphism is associated with higher plasma PfHRP2 concentrations, lower parasite densities and a higher sequestration index. We provide testable hypotheses for the mechanism of protection of ATP2B4.